(untitled) (Journal of Parents and Teachers, 2024)
The concept of the meaning of life has a long tradition in philosophical reflection, but in recent years, its relevance has grown exponentially across various fields of knowledge. Education, in particular, has not remained untouched by this rising interest. Is meaning found, achieved, or learned? Discovering or having a sense of purpose in life is no small matter, yet it becomes clear that merely conceptualizing or privately defining it is not enough. Attaining or grasping this meaning requires understanding the "how." This article, therefore, explores the connections between the concept of meaning in life and education, approached through the lens of the philosophy of education.